2004
DOI: 10.1074/jbc.m314124200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Modifications and Down-regulation of Ubiquitin Carboxyl-terminal Hydrolase L1 Associated with Idiopathic Parkinson's and Alzheimer's Diseases

Abstract: Alzheimer's disease (AD) and Parkinson's disease (PD) are the two most common neurodegenerative diseases that occur either in relatively rare, familial forms or in common, sporadic forms. The genetic defects underlying several monogenic familial forms of AD and PD have recently been identified, however, the causes of other AD and PD cases, particularly sporadic cases, remain unclear. To gain insights into the pathogenic mechanisms involved in AD and PD, we used a proteomic approach to identify proteins with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
382
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(403 citation statements)
references
References 39 publications
15
382
0
6
Order By: Relevance
“…We determined that UCH-L1 protein levels were reduced approximately twofold in the brain extracts of the HEXBÀ/À animals when compared to the wild-type animals. Recent data indicated that in the brains of patients affected with Alzheimer's disease and Parkinson's disease, UCH-L1 undergoes post-translational modifications such as carbonylation, methionine oxidation and cysteine oxidation, 21 which significantly alter its activity. Our experiments also detected the presence of the UCH-L1 isoforms with three oxidized methionine residues, but the ratio between modified and nonmodified protein was similar for HEXB þ / þ and HEXBÀ/ À animals (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…We determined that UCH-L1 protein levels were reduced approximately twofold in the brain extracts of the HEXBÀ/À animals when compared to the wild-type animals. Recent data indicated that in the brains of patients affected with Alzheimer's disease and Parkinson's disease, UCH-L1 undergoes post-translational modifications such as carbonylation, methionine oxidation and cysteine oxidation, 21 which significantly alter its activity. Our experiments also detected the presence of the UCH-L1 isoforms with three oxidized methionine residues, but the ratio between modified and nonmodified protein was similar for HEXB þ / þ and HEXBÀ/ À animals (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…However, we and others have shown that S-nitrosylation and further oxidation of parkin, a ubiquitin E3 ligase, or UCH-L1, a deubiquitinating enzyme that recycles ubiquitin, results in dysfunction of these enzymes and thus of the UPS. 17,20,[68][69][70][71] We found that nitrosative stress triggers S-nitrosylation of parkin (forming SNO-parkin) not only in rodent models of PD but also in the brains of human patients with PD and Lewy bodies. SNO-parkin initially stimulates ubiquitin E3 ligase activity, resulting in enhanced ubiquitination, as observed in Lewy bodies, followed by a decrease in enzyme activity, producing a futile cycle of dysfunctional UPS (Figure 2).…”
Section: S-nitrosylation As a Potential Positive Regulator Of Excitotmentioning
confidence: 99%
“…15 Furthermore, Nishikawa et al 17 found that oxidation of UCH-L1 by 4-hydroxynonenal (a putative endogenous mediator of oxidative stress) results in loss of hydrolase activity. In a complementary study, Choi et al 16 identified an oxidized form of UCH-L1 in sporadic PD brains. Decreased UCH-L1 activity could potentially contribute to UPS dysfunction, accumulation of damaged proteins, and formation of aggregates.…”
Section: Genetic Mutations Link Dysfunction Of Ubiquitination To Pdmentioning
confidence: 99%
“…Interestingly, four studies have provided mounting evidence that nitrosative or oxidative stress results in the malfunction of parkin and UCH-L1 via S-nitrosylation or oxidation, and thereby contributes to the pathogenesis of the sporadic form of PD. [14][15][16][17] S-nitrosylation (SNO) is a redox-based modification of specific cysteine thiol groups, whereby nitric oxide (NO) reacts with thiol to form an SNO-protein, and thus regulates protein activity. 18,19 We and others recently reported that the RING-finger E3 ligase, parkin, is S-nitrosylated in the brains of human patients with PD as well as in rodent brains of models of the disease.…”
Section: Genetic Mutations Link Dysfunction Of Ubiquitination To Pdmentioning
confidence: 99%